2021
DOI: 10.46542/pe.2021.211.781788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacists' scope of knowledge for medication therapy management in chronic kidney disease patients

Abstract: Medication therapy management (MTM) was first implemented and introduced for chronically ill patients and those taking multiple prescription drugs. The MTM has five steps, namely medication therapy review (MTR), personal medication record (PMR), medication-related action plan (MAP), intervention or referral, and finally, documentation. After receiving MTM services, patients will gain knowledge on medicines, which may decrease non-adherence to treatment and increase its efficacy. Studies have shown the positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“… 24 , 25 To improve the quality of pharmaceutical care for pre-ESRD patients, we adopted a MTM model proven abroad to effectively improve the clinical disease control, medication adherence, and quality of life of CKD patients. 15 The factors affecting medication adherence include patient-related factors (such as misconceptions about medication information and lack of medication-related self-efficacy), medication-related factors (such as polypharmacy), health care system-related factors (such as lack of trust in doctors by patients), and socio-economic factors (such as lack of social support and low education levels), all of which may lead to a decline in medication compliance. 23 , 26 Previous research has found that health care professionals can help patients improve their medication compliance by incorporating medication administration into regular daily life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 , 25 To improve the quality of pharmaceutical care for pre-ESRD patients, we adopted a MTM model proven abroad to effectively improve the clinical disease control, medication adherence, and quality of life of CKD patients. 15 The factors affecting medication adherence include patient-related factors (such as misconceptions about medication information and lack of medication-related self-efficacy), medication-related factors (such as polypharmacy), health care system-related factors (such as lack of trust in doctors by patients), and socio-economic factors (such as lack of social support and low education levels), all of which may lead to a decline in medication compliance. 23 , 26 Previous research has found that health care professionals can help patients improve their medication compliance by incorporating medication administration into regular daily life.…”
Section: Discussionmentioning
confidence: 99%
“… 12–14 Incorporating medication therapy management (MTM) through pharmacists has demonstrated potential to enhance patient medication adherence, mitigate healthcare costs, and improve CKD patients’ quality of life. 15 Prior research has indicated that pharmacist interventions for both inpatients and outpatients with CKD can resolve medication-related problems (MRPs), promote medication adherence, and improve disease control. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the critical roles of pharmacists in the eld of community pharmacies and hospitals is to provide medication therapy management (MTM) services. MTM means a thorough review of the patient's medication therapy, including a comprehensive review of medication history (including all over-the-counter, prescribing drugs, and supplements used or currently used by the patient), solving medication-related problems (MRPs), optimizing complex treatment strategies, management of polypharmacy, designing high-adherence medication regimes, and cost-effective treatment schedules (3,(7)(8)(9)(10)(11). The ultimate goal of MTM is to optimize pharmacotherapy consequences, minimize medication errors, and improve the HRQoL and the patient's health status (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the irreversible and complex etiology of CKD, the treatment approach is to manage and break the progression of the disease (19). The role of clinical pharmacists in providing MTM for CKD patients is crucial because these patients face high rates of MRP and medication rejection, more vulnerability to drug poisoning, a high probability of drug-drug interactions (DDIs), comorbidities (such as diabetes, hypertension, osteopathy, anemia, and electrolyte instabilities) due to the possible progression of CKD, and the need to dose adjustment of medications with renal elimination (9,20,21). This survey was aimed to assess the knowledge, attitude, performance, and adherence of CKD patients to the clinical pharmacist-provided MTM in Tehran, Iran, before and after receiving this service.…”
Section: Introductionmentioning
confidence: 99%